Analisis Kebutuhan untuk Menumbuhkan Kemampuan Interaksi Sosial Anak ABK Melalui Program BK - Lindiani, Kholifah; Hajar, Siti (LPPM Institut Pendidikan Nusantara Global, 2025)
This research is a descriptive qualitative study aimed at understanding the social interaction abilities of students with special needs (SEN) in schools, as well as the role of the Guidance and Counseling (GC) program in fostering these abilities. The research subjects included the GC teacher, principal, vice principal, SEN students, their peers, and the parents of SEN students. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The findings indicate that the school adopts an inclusive approach, providing a special admission pathway for SEN students during enrollment and offering opportunities for participation in school activities such as art performances and Islamic holiday celebrations. GC teachers play an active role in providing individualized counseling services tailored to the needs of the students, and in building communication with homeroom teachers and parents. The social interaction skills of SEN students develop gradually within the school's inclusive and supportive environment. The implemented GC programs are not significantly different from those for regular students but still take into account the individual needs of SEN students. Collaboration between GC teachers, the school, and parents plays a crucial role in supporting the development of the students' social skills.